Estudio iconográfico del menologio en San Pedro de Treviño - Gorka López de Munain Iturrospe (Brocar. Cuadernos de investigación histórica, 2008)
The sixth archivolt of the church of Treviño has been the subject of many studies because of its singular iconography and its difficult interpretation. Along the archivolt appears the cycle of the labors of the month and zodiacal signs but it isn´t complete. In consequence, many studious tried to explain the portal in several directions. With this work we would try to bring new facts studying the iconography of the figures and their precedents in order to explain the whole portal in a coherent way.